Empire of pictures: global media and the 1960s remaking of American foreign policy (Explorations in culture and international history series; volume 8) - Kunkel, Sönke (Explorations in culture and international history, 2015)
In Cold War historiography, the 1960s are often described as a decade of mounting diplomatic tensions and international social unrest. At the same time, they were a period of global media revolution: communication satellites compressed time and space, television spread around the world, and images circulated through print media in expanding ways. Examining how U.S. policymakers exploited these changes, this book offers groundbreaking international research into the visual media battles that shaped America's Cold War from West Germany and India to Tanzania and Argentina.